Opioid analgesia and temperature regulation are associated with EEG background activity and MRI outcomes in neonates with mild-to-moderate hypoxic-ischemic encephalopathy undergoing therapeutic hypothermia. (July 2022) - Mahdi, Zamzam; Marandyuk, Bohdana; Desnous, Beatrice; Liet, Anne-Sophie; Chowdhury, Rasheda Arman; Birca, Veronica; Décarie, Jean-Claude; Tremblay, Sophie; Lodygensky, Gregory Anton; Birca, Ala; Pinchefsky, Elana F.; Dehaes, Mathieu
Abstract: Background: Therapeutic hypothermia (TH) without sedation may lead to discomfort, which may be associated with adverse consequences in neonates with hypoxic-ischemic encephalopathy (HIE). The aim of this study was to assess the association between level of exposure to opioids and temperature, with electroencephalography (EEG) background activity post-TH and magnetic resonance imaging (MRI) brain injury in neonates with HIE. Methods: Thirty-one neonates with mild-to-moderate HIE who underwent TH were identified. MRIs were reviewed for presence of brain injury. Quantitative EEG background features including EEG discontinuity index and spectral power densities were calculated during rewarming and post-rewarming periods. Dose of opioids administered during TH and temperatures were collected from the medical charts. Multivariable linear and logistic regression analyses were conducted to assess the associations between cumulative dose of opioids and temperature with EEG background and MRI while adjusting for markers of HIE severity. Results: Higher opioid doses ( β  = −0.21, p  = 0.02) and reduced skin temperature ( β  = 0.14, p  < 0.01) were associated with lower EEG discontinuity index recorded post-TH. Higher opioid doses ( β  = 0.75, p  = 0.01) and reduced skin temperature ( β  = −0.39, p  = 0.02) were also associated with higher EEG Delta power post-TH. MRI brain injury was observed in 14 patients (45%). In adjusted regression analyses, higher opioid doses (OR = 0.00; 95%CI: 0–0.19; p  = 0.01), reduced skin temperature (OR = 41.19; 95%CI: 2.27–747.86; p  = 0.01) and reduced cooling device output temperature (OR = 1.91; 95%CI: 1.05–3.48; p  = 0.04) showed an association with lower odds of brain injury. Conclusions: Higher level of exposure to opioids and reduced skin temperature during TH in mild-to-moderate HIE were associated with improved EEG background activity post-TH. Moreover, higher exposure to opioids, reduced skin temperature and reduced device output temperature were associated with lower odds of brain injury on MRI. Highlights: Opioid analgesia may affect temperature regulation processes in neonates with HIE during therapeutic hypothermia. Exposure to opioids and reduced skin temperature were associated with EEG background recovery and lower odds of MRI injury. Reduced cooling device output temperature was associated with lower odds of MRI injury. Findings highlight the importance of further investigating the impact of sedation in milder forms of HIE.